Efficacy of phacoemulsification combined with goniosynechialysis for primary angle closure glaucoma - I. Ia. Novytskyy; R. M. Lopadchak; M. I. Novytskyy (Journal of Ophthalmology, 2020)
Background: To date, no universal surgical strategy exists for primary angle closure glaucoma (PACG).